2000
DOI: 10.1007/s004290000136
|View full text |Cite
|
Sign up to set email alerts
|

Multiarchitectonic characterization of insular, perirhinal and related regions in a basal mammal, Echinops telfairi

Abstract: The rhinal cortex was investigated in the Madagascan lesser hedgehog tenrec, a basal placental mammal. This region parallels the rhinal indentation and presumably contains the equivalents of the insular and perirhinal cortices. Using cyto- and myeloarchitectural, enzyme- and immunohistochemical criteria as well as data on the connections with the olfactory bulb, the rhinal cortex was subdivided tentatively along its rostrocaudal and dorsoventral planes. An area caudally adjacent to the rhinal cortex received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
2
19
0
Order By: Relevance
“…The latter's 6-layered structure [Brodmann, 1909] first evolved in early mammals before subsequent surface expansion occurred (some insectivores and afrotherians continue to have very little neocortex) [Künzle and Radtke-Schuller, 2000]. A fully 6-layered neocortex is reportedly present and probably expanded independently in monotremes [Krubitzer, 1998[Krubitzer, , 2009Hassiotis et al, 2005].…”
Section: Structure Of the Pallium And The Planar Signaling Involved Imentioning
confidence: 99%
See 1 more Smart Citation
“…The latter's 6-layered structure [Brodmann, 1909] first evolved in early mammals before subsequent surface expansion occurred (some insectivores and afrotherians continue to have very little neocortex) [Künzle and Radtke-Schuller, 2000]. A fully 6-layered neocortex is reportedly present and probably expanded independently in monotremes [Krubitzer, 1998[Krubitzer, , 2009Hassiotis et al, 2005].…”
Section: Structure Of the Pallium And The Planar Signaling Involved Imentioning
confidence: 99%
“…They occupy a deep position corresponding to layer VIb, with some dispersion into the overlying layers (mainly layers VIa and V), and are described as 'modified pyramids'. One clear-cut example is represented by Nurr1 -expressing cells [Arimatsu et al, 2003], a subgroup of which also express latexin, a carboxypeptidase A inhibitor [Arimatsu et al, , 1999a[Arimatsu et al, , b, 2009Hatanaka et al 1994;Künzle and Radtke-Schuller, 2000;Liu et al, 2000;Takiguchi-Hayashi, 2001;Arimatsu and Ishida, 2002]. Latexin-positive neurons seem to be involved in ipsilateral cortico-cortical associative feedback connectivity [Bai et al, 2004], which possibly reveals a pallio-pallial hodological property also shared by claustro-cortical connections [Crick and Koch, 2005].…”
Section: Implications Of the Cr-pallial And Ventropallioneopallial MImentioning
confidence: 99%
“…The mammalian insula is currently understood as enclosing multiple sensorimotor and associative subareas [review in Nieuwenhuys, 2014; see also Burwell et al, 1995;Künzle and Radtke-Schuller, 2000]; as commented above, these connections and functions might bear comparison with the avian mesopallial data of Atoji and Wild [2012]. Moreover, the disgranular insular cortex receives gustatory and visceral input from the parabrachial nucleus, as well as some direct olfactory projections [Shipley and Geinisman, 1984;Lundy and Norgren, 2004;Whitehead, 2012].…”
Section: Connectivity Of the Claustro-insular Lpall With Thoughts Onmentioning
confidence: 99%
“…1 shows the medial (A,C), dorsal (A,C) and lateral (B) views of the Echinops' cerebral hemisphere, its neocortical, rhinal and paleocortical subdivisions as well as the cortical zones used for the description of the results in absence of distinct cytoarchitectural boundaries. These zones are defined on the basis of proportional coordinates (ppc) taken from the reference distance between the rostral pole of the cerebral hemisphere (ppc 0) and the point where the hemispheres diverge from each other (ppc 1.0; for further details see Künzle and Radtke-Schuller 2000c). References to these coordinates, however, should not be interpreted too rigorously; they represent approximate levels that vary due to individual variations and differences in the plane of sectioning of this small brain (average length of the reference distance is 5.4 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent tracer studies, however, showed (Künzle 2002) that the area projecting to the dentate gyrus only involves a minor portion of the dorsal PCx but extends considerably into the rhinal cortex (RCx) and the caudally adjacent area XCx ( Fig. 1B; see also Künzle and Radtke-Schuller 2000c). It is known that the presumed equivalents of RCx and XCx in other species, the perirhinal and postrhinal cortices project to the hippocampus (Kosel et al 1983;Suzuki and Amaral 1990;Naber et al 1999), but never to the extent and the intensity as shown from the tenrec's RCx/XCx and only to the cornu ammonis and the subiculum, and not to the dentate area.…”
Section: Introductionmentioning
confidence: 96%